Prevalence, risk factors and adverse pregnancy outcomes of second trimester bacterial vaginosis among pregnant women in Bukavu, Democratic Republic of the Congo - Guy Mulinganya (Public Library of Science (PLoS), 2021)
Background Bacterial vaginosis (BV) is the most common gynecological condition in women of reproductive age and associated with adverse pregnancy outcomes. In the Democratic Republic of the Congo (DRC), neonatal mortality rate is as high as 2.8 percent with preterm birth (PTB) and low birth weight (LBW) as leading causes. Because no studies have addressed BV in DRC, we aimed to investigate the prevalence of BV, the risk factors and the association between BV and adverse pregnancy outcomes in a population of pregnant women from Bukavu, DRC. Methods A total of 533 pregnant women in the second trimester of pregnancy were recruited in the Provincial Reference Hospital of Bukavu, DRC, between January and October 2017, and followed until delivery. Clinical and sociodemographic data of mother and newborn, and data on (vaginal) hygiene practices, sexual behavior and reproductive history were collected. BV was diagnosed by Nugent scoring of Gram-stained vaginal smears. Two multivariate regression models were built to identify risk factors for BV and to investigate BV as a risk factor for adverse pregnancy outcomes. Results The prevalence of BV was 26.3% and approximately half of the women with BV were asymptomatic. Independent risk factors for BV were the use of alternatives to water for intravaginal washing, concurrent partners, unemployed status, the presence of vaginal Candida and clay consumption. BV was independently associated with both LBW and PTB of an infant with LBW. Conclusion The prevalence of BV in Bukavu is high but in line with the global average. BV was associated with adverse pregnancy outcomes in our study population. Hence, research on modifiable risk factor-based interventions to reduce the prevalence of BV, and on screening/treatment of BV during antenatal care should be explored to reduce neonatal mortality and morbidity.